Effect of solid-state buffers on the catalytic activity of papain in low water media - Theppakorn T. (2014)
The catalytic activity of papain in the synthesis of Z-Gly-Phe-NH2 in tert-butanol has been studied in the presence of solid-state acid-base buffers (acids and their sodium salts). All buffer pairs tested reduced the reaction rate compared with the control, particularly the most acidic and basic (assessed by either aqueous pKa or the response of an organic phase indicator). The highest rates, close to the control, were found with glutamic acid/glutamate-Na, PIPES/PIPES-Na and NaH2PO4/Na2HPO4. However, these pairs were unable to erase the pH memory phenomenon, or to overcome the effect of spiking with acetic acid. Hence, at least these buffers do not seem to be able to affect the protonation state and catalytic activity of papain. In the last aqueous solution before drying, the presence of activating agents (cysteine plus EDTA) was more important than buffer ions. © 2003 Elsevier Science Inc. All rights reserved.